QUALITY OF TEACHER'S REFLECTION BASED ON INSTRUMENT CATEGORIES AND LEVEL OF REFLECTION ON LESSON STUDY ACTIVITIES AT SD GAGASCERIA - Melia Rudonaviola (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2021)
Reflection becomes an important moment in lesson study because there is a pause with the process that has occurred to review the learning activities that have been carried out. This has an impact in determining the next follow-up in designing learning. This reflection stage is very important because efforts to improve the next learning process will depend on the sharpness of the analysis from participants' reflection. Reflection activities are carried out in the form of discussions which are followed by all lesson study participants guided by the principal or other appointed participants. The purpose of this study is to analyze the quality of reflection in post lesson discussions at SD GagasCeria so that it will affect the next learning design based on the learning process obtained by each participant. The research was conducted at SD GagasCeria using qualitative methods based on data analysis of post lesson discussion documents during lesson study in the 2018-2019 school year and 2020-2021 school year. Lesson study activities were carried out in 3 different classes attended by the teachers of SD GagasCeria. The reflection analysis instruments used are categories and levels designed to measure post-learning reflection from Ono (2013). Based on the results of the analysis of the post lesson discussion notes, there is a change in the level of reflection in 2019 and 2021. In 2019, the teacher's reflection level at GagasCeria is at level 1, which describes data and facts in general. In 2021, the teacher reflection level at GagasCeria increases to level 2 by 24%. At level 2, in addition to conveying the data and facts obtained, the possible background or reasons were also explained. This reflection analysis can be a reference in improving the quality of subsequent learning and developing teacher professionalism.Keyword:  categories and levels of reflection, lesson study, reflection